Development of a feature-rich, practical online application for the Training and Placement Dept. of the college - Ramesh, Mareedu (International Journal of Computer Sciences and Engineering, 2014)
This project is aimed at developing an online application for the Training and Placement Dept. Of the college. The system is an online application that can be accessed throughout the organization and outside as with proper login provided. This system can be used application for the TPO of the college to manage the student can be information with regards to placement. Students logging should be able to upload their information in the form of a CV. Visitors/Company representatives logging in may also access/search any information put up by Students.